Student's toolbox : tips for better writing - Spilsbury, Louise (New York : Gareth Stevens Publishing, 2014)
Provides tips on how students can improve their writing.
Includes bibliographical references : (page 31) and index.
Keywords: English language -- Composition and exercises -- Juvenile literature; English language -- Composition and exercises